ROUTLEDGE HANDBOOK OF SPORT IN CHINA - Fan, Hong, 1957-; Li, Liu. ([S.l.] : ROUTLEDGE, 2023)
This is the first book to offer a comprehensive overview of the history and development of sport from the ancient to the contemporary era in China. It addresses the gap between the vibrant academic scholarship within China and the limited understanding of Chinese sport outside of the country. It opens different perspectives on Chinese sport and addresses a wide range of issues central to the development of sport in the context of Chinese culture, politics, economy, and society. It explores a diverse set of topics including the history of Chinese traditional sport, the rise of modern sport and the Olympic movement, sport and nationhood, sport and politics and international relations, sport and physical education, sport and economy and commerce, sport and social stratification and diversity, and sport leisure and tourism. It offers critical insights into the multifaceted world of China, past and present--a contribution to our collective knowledge and understanding of Chinese sport and society--and is useful reading for students, researchers, and professionals with an interest in the field of China and Chinese sport. This Handbook has been contributed to by a team consisting of 88 leading Chinese and Asian experts and scholars with varied backgrounds of studying and working in European, North American, and Australian universities, as well as Western scholars with expertiseon China and its sports system and practice. It is composed of ten parts classified by different subjects. It provides a wide lens through which to better contextualise the relationships between China and the world within the global sport community. The Routledge Handbook of Sport in China is a vital resource for students and scholars studying the history, politics, sociology, culture and policy of sport in China, as well as sport management, sport history, sport sociology, and sport policy and politics. It is also valuable reading for those who are working in international sport policy making and sport organisations.
Keywords: SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; SPORTS & RECREATION / Sociology of Sports; Sports -- China -- History